A Comprehensive Review of Carbon-Based Materials for Energy Storage Devices: Types and Characterization Techniques - Escobar-Teran, Freddy; Perrot, Hubert; Sel, Ozlem (Science and Technology: Recent Updates and Future Prospects Vol. 9, 2024)
Nowadays, there are different types of supercapacitors in terms of charge-storing mechanisms. The urgent need for efficient energy storage devices (supercapacitors and batteries) has attracted ample interest from scientists and researchers in developing materials with excellent electrochemical properties. Conducting polymers (CPs), transition metal oxides, and carbon have all been utilized as electrode materials. Among these materials, carbon has drawn a lot of interest for use in Electrochemical Double-Layer Capacitors (EDLC) because of its exceptional electrical and mechanical qualities, as well as its changeable pore shape and structural characteristics. In this context, the present review article summarizes the history of supercapacitors and the basic function of these devices, the type of carbon electrode materials, and the different strategies to improve the performance of these devices. In addition, we present different approaches to studying the charging mechanism of these devices through different electrochemical techniques existing in the literature, since a deeper understanding of the interfacial charge storage mechanisms is also crucial in the elaboration and performance of the electrode material. We contrast the various methods and outline the benefits and drawbacks of each. Considering these developments, we believe that combining two approaches/techniques leads to a deeper comprehension of the charge storage mechanisms in energy storage devices. The choice of type of material and electrolyte ion to improve the performance of the supercapacitor electrodes has been widely studied in the literature. However, the choice of a characterization technique that allows us a deeper understanding of the interfacial charge storage mechanisms is also crucial in the elaboration and performance of the electrode material.